Essential Java for scientists and engineers - Hahn, Brian D. (Butterworth-Heinemann, 2002)
This text serves as an introduction to the programming language Java for scientists and engineers, as well as experienced programmers wishing to learn Java as an additional language. The authors have specifically taken a hands-on approach to get the reader writing and running programs immediately. In addition, the book focuses on how Java, and object-oriented programming, can be used to solve science and engineering problems. Many examples are included throughout, from a number of different scientific and engineering areas, as well as from business and everyday life, which demonstrate the prac.